World record extreme sea surface temperatures in the northwestern Arabian/Persian Gulf verified by in situ measurements. (December 2020) - Alosairi, Y.; Alsulaiman, N.; Rashed, A.; Al-Houti, D.
Abstract: The Arabian or Persian Gulf is recognized as one of the warmest estuaries globally. The sea surface temperature (SST) has been utilized in several studies to gauge the global warming associated with climate change. In the current investigation we present detailed in situ SST measurements for five consecutive years (2016, 2017, 2018, 2019, 2020) in the northwest of the Gulf, specifically in Kuwait Bay. Results of data analyses were compared with the historical records for the region, revealing that the SST reached an extreme level never previously recorded either in the Gulf. The extreme SST in Kuwait Bay reached 37.6 °C, recorded by the offshore station KISR01 located in the middle of the Bay. The event was associated with heatwave, neap tides, and an extended period of Kous winds which are characterized by high humidity levels and accompanied by large-scale intermittent fish kill incidents that extended the full length of the Kuwait coastline. Several fish kill incidents were reported also at the northern edge of the Gulf along Shatt Al Arab stretch in Iraq. The species found dead during the incident varied considerably, unlike those found in the frequent summer incidents. The records presented in this study may provide evidence to the effects of global warming, aid further research, and encourage the concerned international government bodies to deliver urgent environmental policies. Graphical abstract: Unlabelled Image Highlights: Detailed measurements of SST were conducted from 2016 to 2020. Extreme SST was recorded in the offshore regions. The extreme SST reached 37.6 °C was never recorded previously. The high SST was accompanied by major fish kill incidents. Extreme SST might be associated with COVID19 circumstances.